PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE, PROFITABILITAS, DAN LEVERAGE TERHADAP EARNING MANIPULATION DENGAN MODERASI KUALITAS AUDIT - F. Agung Himawan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 observation period, as many as 45 companies. The sampling method used in this research is purposive sampling. The hypothesis in this study was tested using multiple linear regression analysis to measure the effect of the relationship between the dependent variable and the independent variable. This study aims to analyze empirically the GCG variables (KM, KI, Audsize and Bdout) as well as Profitability proxied by ROA, Leverage as proxied by DER, on Earning Manipulation proxied by Beneish M Score with Audit Quality as a moderating variable in manufacturing companies that listed on the Indonesia Stock Exchange for the period 2014-2018 with a sample of 45 companies and 225 firm years. The results of this study indicate that the Beneish M score is significantly influenced by Managerial Ownership, Institutional Ownership, Audsize, and profitability (ROA), the KM variable has a significant negative effect on Earning Manipulation (Beneish M score) at =1%. That is, the higher the management ownership, the lower the indication of manipulation of financial statements. The KI variable has a significant negative effect on earning manipulation, meaning that the more institutional ownership there is, the less manipulation of financial statements occurs. Audsize variable has a significant negative effect on Earning Manipulation (beneish M Score) at =5%. That is, the more audit committees, the higher the supervision which results in no manipulation of financial statements. And lastly, the profitability variable has a significant positive effect on earning manipulation, meaning that the higher the level of profitability of an entity, the more indications there are of financial statement manipulation. The results of model 2 research show that the existence of audit quality as a moderating variable can affect the relationship between KM, KI, Audsize, Bdout, ROA and DER, on earning manipulation (beneish m score). Where the existence of audit quality (QA) weakens the influence of almost all variables on earning manipulation (beneish m score) except for the existence of an independent board of commissioners whose audit quality strengthens the supervision carried out on corporations to avoid earning manipulation and is useful information for investors and investors. stakeholders who use financial statements and these factors are considered by investors and stakeholders to obtain more relevant information.